2011
DOI: 10.1177/0961203310382430
|View full text |Cite
|
Sign up to set email alerts
|

Do subjective cognitive complaints correlate with cognitive impairment in systemic lupus erythematosus? A Danish outpatient study

Abstract: This study examined the prevalence of cognitive impairment and its association with depressive symptoms and self-reported cognitive complaints in Danish outpatients with systemic lupus erythematosus (SLE). Fifty-seven consecutive female SLE-outpatients were examined with a comprehensive neuropsychological test-battery, a 20-item self-administered Perceived Deficits Questionnaire (PDQ) and a self-rated depression scale (Major Depression Inventory). Twenty-two patients (38.5%) were classified as cognitively impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 41 publications
2
28
0
Order By: Relevance
“…Two self-report instruments, the Cognitive Failures Questionnaire (CFQ) and the Perceived Deficits Questionnaire-Short Form (PDQ), have been used in patients with rheumatic disease but neither questionnaire has been validated in patients with SS 41,42,43 . The CFQ was meant to identify lapses in memory, attention, and action 44 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two self-report instruments, the Cognitive Failures Questionnaire (CFQ) and the Perceived Deficits Questionnaire-Short Form (PDQ), have been used in patients with rheumatic disease but neither questionnaire has been validated in patients with SS 41,42,43 . The CFQ was meant to identify lapses in memory, attention, and action 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Absence of cognitive complaints does not exclude the presence of cognitive problems. Vogel, et al reported in a study of Danish patients with SLE that the level of subjective cognitive complaints was low even among patients with cognitive impairment 41 . If the clinical context warrants, formal neuropsychological evaluation should be considered even in the absence of cognitive complaints.…”
Section: Rheumatologymentioning
confidence: 99%
“…Problems with accuracy in selfreported cognitive symptoms are seen in a variety of health conditions, including cognitive functioning after cancer treatment [1], systemic lupus erythematosus [2], epilepsy [3], multiple sclerosis [4], Parkinson disease (PD) [5], and schizophrenia [6]. This reduced accuracy is generally related to overreporting of symptoms, but varies according to the condition.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Reports on the PDQ have similarly been found to be related to concomitant reports of depression. 15 Moreover, in a recent study examining the PDQ in a population of patients with lupus, who tend to underreport cognitive concerns, Vogel et al 16 observed a high correlation between subjective cognitive concerns as measured by the PDQ and self-rated depressive symptoms. Together, these findings suggest that mean (SD) amount of education was 15.5 (2.47) years (Table 1).…”
mentioning
confidence: 99%